Lactiplantibacillus plantarum IS-10506 Enhances Tight Junction Integrity in Bronchial Epithelium: An Experimental Study - Deasy Fetarayani; Gatot Soegiarto; Ingrid Suryanti Surono; Anang Endaryanto; Alpha Fardah Athiyyah; Yetti Hernaningsih; Dyah Fauziah; I Ketut Sudiana; Budi Utomo; Cita Rosita Sigit Prakoeswa (Indonesian Biomedical Journal, 2024)
BACKGROUND: Airway epithelium constitutes the initial structural defense against inhaled allergens, with its integrity primarily maintained through the formation of tight junctions (TJ) consisting of claudins, occludins, and zonula occludens (ZO). Currently, the effects of probiotics on airway TJ remain unclear. Therefore, this study was conducted to explore the impact of Lactiplantibacillus plantarum IS-10506, a native probiotic from Indonesia, on bronchial epithelial TJ in a mouse model of allergic airway inflammation.